Association of hip pain with radiographic evidence of hip osteoarthritis: diagnostic test study. (2nd December 2015) - Kim, Chan; Nevitt, Michael C; Niu, Jingbo; Clancy, Mary M; Lane, Nancy E; Link, Thomas M; Vlad, Steven; Tolstykh, Irina; Jungmann, Pia M.; Felson, David T; Guermazi, Ali
Abstract : Study question Is there concordance between hip pain and radiographic hip osteoarthritis? Methods In this diagnostic test study, pelvic radiographs were assessed for hip osteoarthritis in two cohorts: the Framingham Osteoarthritis Study (community of Framingham, Massachusetts) and the Osteoarthritis Initiative (a multicenter longitudinal cohort study of osteoarthritis in the United States). Using visual representation of the hip joint, participants reported whether they had hip pain on most days and the location of the pain: anterior, groin, lateral, buttocks, or low back. In the Framingham study, participants with hip pain were also examined for hip pain with internal rotation. The authors analysed the agreement between radiographic hip osteoarthritis and hip pain, and for those with hip pain suggestive of hip osteoarthritis they calculated the sensitivity, specificity, positive predictive value, and negative predictive value of radiographs as the diagnostic test. Study answer and limitations In the Framingham study (n=946), only 15.6% of hips in patients with frequent hip pain showed radiographic evidence of hip osteoarthritis, and 20.7% of hips with radiographic hip osteoarthritis were frequently painful. The sensitivity of radiographic hip osteoarthritis for hip pain localised to the groin was 36.7%, specificity 90.5%, positive predictive value 6.0%, and negative predictive value 98.9%. Results did not differ much for hip pain at other locations or for painful internal rotation. In the Osteoarthritis Initiative study (n=4366), only 9.1% of hips in patients with frequent pain showed radiographic hip osteoarthritis, and 23.8% of hips with radiographic hip osteoarthritis were frequently painful. The sensitivity of definite radiographic hip osteoarthritis for hip pain localised to the groin was 16.5%, specificity 94.0%, positive predictive value 7.1%, and negative predictive value 97.6%. Results also did not differ much for hip pain at other locations. What this study adds Hip pain was not present in many hips with radiographic osteoarthritis, and many hips with pain did not show radiographic hip osteoarthritis. Most older participants with a high suspicion for clinical hip osteoarthritis (groin or anterior pain and/or painful internal rotation) did not have radiographic hip osteoarthritis, suggesting that in many cases, hip osteoarthritis might be missed if diagnosticians relied solely on hip radiographs. Funding, competing interests, data sharing See the full paper on thebmj.com for funding. The authors have no competing interests. Additional data are available from bevochan@bu.edu .